ROLE OF TUBERCULIN TEST AS A DIAGNOSTIC TOOL FOR TUBERCULOSIS - Rehman, Mujeeb Ur; Bibi, Saima; Imran, Imran; Khan, Zahid; Khan, Ahmed Saeed; Gilani, Syed Yasir Hussain (Journal of Ayub Medical College Abbottabad, 2018)
Background: Childhood Tuberculosis remains one of the major public health concerns in developing countries like Pakistan and is responsible for high rates of morbidity and mortality in children. Although tuberculin skin test is very commonly used by physicians all over the world, its interpretation always remains difficult and challenging. The objective of this study was to determine the frequency of positive tuberculin skin test in vaccinated and unvaccinated children suffering from tuberculosis. Methods: This Cross-sectional study was conducted in the department of Paediatric Ayub Teaching Hospital, Abbottabad from 1st February 2015 to 30th April 2016. A total of 150 patients were observed in this study. Children of either gender who were aged 1-15 years admitted in ward with tuberculosis were included in the study by using non-probability convenient sampling technique. We injected 0.1 ml (10 units) of tuberculin purified protein derivative (PPD) into the anterior surface of the forearm and induration was read at 72 hours after administration. Data was entered and analysed using SPSS version 10. Results: Out of 150 children, 84 (56%) were males and 66 (44%) were females. The mean age was 7.8±3.84 years. Of these 75 (50%) were vaccinated and 75 (50%) were unvaccinated. In vaccinated Group 5.3% children had positive tuberculin skin test while in unvaccinated Group 2.7% children had positive tuberculin skin test and this difference was found statistically insignificant (p-value=0.40). Pulmonary TB was the diagnosis in 67 (44.7%), TBM in 65 (43.3%), abdominal TB in 7 (4.7%), disseminated TB in 4 (2.7%) and military TB in 7 (4.7%) patients. Conclusions: The positivity of tuberculin skin test in vaccinated and unvaccinated children suffering from tuberculosis was found to be insignificant in our study. We conclude that Tuberculin Skin Test should not be used as a sole diagnostic tool for diagnosing the disease in children of our region. Keywords: Vaccinated; Unvaccinated; Tuberculin skin test; Children; Tuberculosis